Cognitive theories in self-transcreation studies: Conceptual equivalence in Tagore’s Bengali and English poems - Tuczyńska, Joanna (Yearbook of the Poznan Linguistic Meeting, 2025)
This paper explores the application of cognitive methodologies, Conceptual Metaphor Theory (CMT) and Conceptual Integration Theory (CIT) in the analysis of cultural equivalence attained in the process of transcreation on the example of Rabindranath Tagore’s Bengali and English poems. CMT tools allow for the re-creation of conceptual interrelations between the Bengali source text and the English target text, which reveals that the metaphorical context in the transcreated version is equivalent. CIT schemas complement cognitive analysis by reconstructing the thought process behind transcreation and revealing a consistent transcreation framework. Examples of the interdependence of CMT and CIT in the reconstruction of conceptual processes are the Bengali metaphorical blends yāōẏā āsā, ‘going-coming’ and khelā melā, ‘game/play-fair/assemblage’, integrated and transformed through the transcreation medium, the hide-and-seek metaphorical blend, into conceptually equivalent context in the target text. The analysis reveals a process of conceptual integration in which the source context is expressed through a transcreation medium, a metaphorical tool recognizable in the target culture, to convey an aesthetically and semantically equivalent message in the target text. CMT and CIT allow for efficient examination of the transcreation process, with the prerequisite that conceptual contexts are approached intertextually.